Human deficiencies of fucosylation and sialylation affecting selectin ligands. - Lühn, K; Wild, M (2012)
Selectins are carbohydrate-binding adhesion molecules that are required for leukocyte trafficking to secondary lymphoid organs and to sites of infection. They interact with fucosylated and sialylated ligands bearing sialyl-Lewis X as a minimal carbohydrate structure. With this in mind, it should be expected that individuals with deficient fucosylation or sialylation show immunodeficiency. However, as this review shows, the picture appears to be more complex and more interesting. Although there are only few patients with such glycosylation defects, they have turned out to be very instructive for our understanding of the functions of fucosylation and sialylation in immunity, development and hemostasis.